2013
DOI: 10.1371/journal.pone.0079077
|View full text |Cite
|
Sign up to set email alerts
|

Acute Physiological Stress Promotes Clustering of Synaptic Markers and Alters Spine Morphology in the Hippocampus

Abstract: GluA2-containing AMPA receptors and their association with protein kinase M zeta (PKMζ) and post-synaptic density-95 (PSD-95) are important for learning, memory and synaptic plasticity processes. Here we investigated these synaptic markers in the context of an acute 1h platform stress, which can disrupt spatial memory retrieval for a short-term memory on the object placement task and long-term memory retrieval on a well-learned radial arm maze task. Acute stress increased serum corticosterone and elevated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
68
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 75 publications
10
68
1
1
Order By: Relevance
“…In addition, the present study provides in vivo evidence that PKMζ overexpression is sufficient to elicit the distribution of plasticity-related proteins and promote long-term memoryassociated alterations of plasticity-related proteins. Our results are consistent with previous in vitro studies that PKMζ overexpression is sufficient to produce the distribution of GluA2 and postsynaptic density-95 and alterations of the morphology and function of dendrite spines (Ron et al, 2012;Sebastian et al, 2013). However, the conclusion of the causal role of PKMζ in the regulation of GluA2 trafficking during memory consolidation should be made with caution.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the present study provides in vivo evidence that PKMζ overexpression is sufficient to elicit the distribution of plasticity-related proteins and promote long-term memoryassociated alterations of plasticity-related proteins. Our results are consistent with previous in vitro studies that PKMζ overexpression is sufficient to produce the distribution of GluA2 and postsynaptic density-95 and alterations of the morphology and function of dendrite spines (Ron et al, 2012;Sebastian et al, 2013). However, the conclusion of the causal role of PKMζ in the regulation of GluA2 trafficking during memory consolidation should be made with caution.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, we found that such a stressor regimen caused significant decreases in dendritic spine density in dendrites of the granule cells in the anterior (or dorsal) dentate gyrus at 6 hours after the conclusion of the stressor regimen. Although chronic stress has been known to produce long-lasting dendritic atrophy in hippocampus [38], a 1-hr platform stress was also reported to cause immediate morphological changes in hippocampus [39]. In parallel with the latter report, our findings indicated that a robust stressor may indeed render morphological changes in the existing granule cells in hippocampal dentate gyrus.…”
Section: An Acute Intense Stressor Causes Rapid Morphological Changesupporting
confidence: 85%
“…As our knowledge on subacute (genomic) and/or post-synaptic modulation of synaptic plasticity by corticosteroids is greatly expanding (Jo€ els et al, 2012;Maggio and Segal, 2012;Sebastian et al, 2013), we asked now if corticosteroids can also serve as fast direct presynaptic neuromodulators, either on their own or involving the CB 1 cannabinoid receptor (CB 1 R).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on neural cell lines and primary cell cultures revealed the complex nature by which McRs and GcRs can trigger spatiotemporally distinct genomic and nongenomic responses, which can lead to changes in the expression and the clustering of pre-and post-synaptic proteins as well as to alterations in dendritic spine morphology (Chatterjee and Sikdar, 2014;Morsink et al, 2006;Sebastian et al, 2013). Of note, dendritic degeneration also occurs in vivo, as documented in the layers C]glutamate, and the lack of dexamethasone effect is unchanged in the CB 1 R KO mice as compared to the WT littermates.…”
Section: Discussionmentioning
confidence: 99%